If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6x + 7) = 49 Reorder the terms: 7(7 + 6x) = 49 (7 * 7 + 6x * 7) = 49 (49 + 42x) = 49 Add '-49' to each side of the equation. 49 + -49 + 42x = 49 + -49 Combine like terms: 49 + -49 = 0 0 + 42x = 49 + -49 42x = 49 + -49 Combine like terms: 49 + -49 = 0 42x = 0 Solving 42x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '42'. x = 0 Simplifying x = 0
| 0.75x+0.5=-0.0625x+0.375 | | 123fu=jop+585+55 | | 4y-16=3y+5 | | 0.5x+70t=2x | | 600(.8)+x=700 | | 15x+22=150 | | 5-2/3x=1/2x-4 | | 7p=-8u | | 4e^1(x^2+1)=0 | | 700+x(.4)=720 | | s(t)=t^2-4/t | | 1200+3x=2100 | | 1250=1/4q | | 2x+6(x+13)=150 | | 900+3x=2100 | | 5x^2+6=-14 | | 2(n-4)/3=5/4 | | 5.5A+5B=26 | | 175+.10m=220+.05m | | 3/5g=3p | | 5.5+5=26 | | 4m-4.2-3m=9.9 | | 5-0.6x=0.5x-4 | | x^2+6x-240=0 | | 5.5+5x=26 | | z=g/4-5 | | -3(y-6)= | | z=g/5-5 | | 8ln(2x)=16 | | (400)(.5)+x(.8)=600 | | 5.5x+5=26 | | -1y+3=8y-7 |